Penugasan Pemerintah pada Badan Usaha Milik Negara Sektor Ketenagalistrikan Dalam Perspektif Hukum Korporasi - Ansari, Muhammad Insa (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2017)
Pemerintah akan mengeluarkan revisi Peraturan Pemerintah tentang Pendirian, Pengurusan, Pengawasan dan Pembubaran Badan Usaha Milik Negara. Melalui aturan ini pemerintah dapat memberikan penugasan khusus bagi BUMN. Fokus pembahasan artikel ini merupakan bidang ketenagalistrikan dan akan membahas mengenai penugasan apa saja yang diberikan oleh pemerintah kepada BUMN sektor ketenagalistrikan, selanjutnya, bagaimana penugasan pemerintah tersebut dalam perspektif hukum korporasi? Penulis berpendapat bahwa penugasan tersebut tidak sejalan dengan perspektif hukum korporasi. Penugasan pemerintah seharusnya diemban oleh BUMN dengan entitas perusahaan umum. Dalam praktik penugasan pemerintah diemban oleh perusahaan perseroan, padahal Undang-Undang Nomor 19 Tahun 2003 tentang BUMN secara tegas dibatasi entitas BUMN berdasarkan maksud dan tujuan, entitas Perum ditujukan untuk mengemban kemanfaatan dan entitas Persero untuk mencari keuntungan.Government Assignment on State-Owned Enterprise on Electricity Sector in Corporate Law PerspectiveAbstractThe Government will soon publish the revision of Ministerial Decree about Establishment, Arrangement, Supervision, and Dismission of State-owned and State-run Enterprises (SOEs). Through this regulation, the government is able to implement special assignments towards SOEs. This article focuses on the field of electrical energy and will describe what kind of assignments that the government ordered to SOEs in electricity sector, and moreover how are the given assignments implied through the prespective of corporate law. The writer argues the special assignments given by the government are not in line with corporate law prespective. The assignments shall be conducted by SOEs under the entity of public companies. In practice, the government assignments are implemented by limited liability companies, even though according to the Law Number 19 Year 2003 about SOEs, it is well-said that SOEsâ functions are limited based on specific purposes, whereas the public company entity is aimed to create advantages for public interests and limited liability company entity is aimed to create profits.Â